Machine learning for predicting silica purity based on the chemical composition and granulometry of sand in the Kyrgyz Republic (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of a study on the influence of chemical composition and granulometric characteristics of quartz raw materials from various deposits in Kyrgyzstan (Tash-Kumyr, Sulyukta, Ozgur) on the purity of metallurgical-grade silicon, using methods of mathematical modeling and elements of machine learning. Elemental analysis revealed significant differences between the deposits: the SiO₂ content in Tash-Kumyr quartz reaches ~94.3 %, while in Sulyukta it does not exceed 85 %, accompanied by a considerably higher level of Al₂O₃ and other impurities. The developed model combines the linear effects of oxide impurities (Al₂O₃, Fe₂O₃, MgO, CaO, K₂O) and a quadratic dependence on particle size, with weight coefficients calibrated using machine learning algorithms. Modeling confirmed that the optimal particle size (0.05 mm) ensures maximum purity, while deviations reduce it by 2–5 %. Predictive curves highlighted the advantage of Tash-Kumyr raw material (up to 98 % purity). The results demonstrate the potential of integrating machine learning to improve prediction accuracy and provide a rational basis for selecting promising deposits.
Keywords: metallurgical-grade silicon, quartz sand, machine learning, modeling, granulometry, impurities, prediction